SOCIAL CRITICISM IN RHYME DILEMA MELAYU PATANI - -Mae, Fateenee Sa; Hasyim, Nafron; Imron, Ali; Sabardila, Atiqa; Markhamah, Markhamah (Jurnal Analisa Sosiologi, 2020)
The objectives of this study are: (1) identify social criticism the author delivers in Kumpulan Sajak Dilema Melayu Patani, and (2) study the relevance of the result as literature teaching material for Senior High School. This is a descriptive qualitative research using library technique for data collection. This research uses soft data in the form of words, phrase, clause and sentences located in the poetry by Phaosan Jehwae which contains social criticism. Data was analyzed using dialectic method. The researchers classify the result of this into social criticism and learning material relevance. The social criticism includes social condition which leads to criticism towards government, economic problems due to assets taken, which lead to poor condition, cultural problems due to changing era, and lack of faith due to foreign cultures. This poetry is found to be relevant as literature learning material, because (a) the language is appropriate with Senior High School students, (b) the content is psychologically appropriate with Senior High School spirits, and (c) socially, these poetries depict oppressed society appropriate with Senior High School students’ desire in fighting for the people. In conclusion, the poetry is relevant as literature learning material and the social criticism helps in that aspect.Keywords: Potry, Social Critism, Literature Learning Material. AbstrakTujuan dalam penelitian ini ada dua, yakni (1) menemukan kritik sosial yang ingin disampai pengarang, dan (2) relevansi hasil penelitian sebagai bahan ajar  dalam pembelajaran sastra di SMA. Metode penelitian yang digunakan adalah deskriptif kualitatif. Teknik pengumpulan data penelitian ini mengguna teknik pustaka. Data penelitian ini berupa data lunak yang berwujud kata-kata, frasa, klausa, dan kalimat yang termuat dalam Kumpulan Sajak Dileme Melayu Patani karya Phaosan Jehwae yang memuat kritik sosial. Teknik analisis data menggunakan metode dialektik. Berdasarkan hasil penelitian, peneliti menyimpulkan dua hal, (1) Kondisi sosial terjadi karena rakyat tidak senang hati terhadap pemerintah yang tidak adil, sehingga menimbul berbagai konflik, masalah ekonomi terjadi karena harta negara dirampas rakyak dalam keadaan miskin, masalah budaya terjadi karena zaman berubah dan kekurangan iman mudah dipengaruhi budaya-budaya asing. (2) Penelitian ini relevan dengan pembelajaran sastra, karena (a) bahasanya sesuai dengan kemampuan siswa SMA,  (b) isinya secara psikologis sesuai dengan semangat juang siswa SMA, dan (c) secara sosial puisi-puisi ini menggambarkan keadaan masyarakat yang sedang tertindas yang sesuai dengan keinginan remaja seusia SMA untuk berjuang demi masyarakat.Kata kunci: Kritik Sosial, Kumpulan Sajak Dilema Melayu Patani, Sosiologi Sastra, Bahan Ajar Sastra.